Pharmacy preparedness in handling COVID-19 pandemic: a sharing experience from a Malaysian tertiary hospital - Kah Shuen Thong; Manimegahlai Selvaratanam; Chiew Ping Tan; Meng Fei Cheah; Hoey Lin Oh; Pooi Mun Lee; Chii-Chii Chew; Chee-Tao Chang; Jason Choong Yin Lee (Taylor & Francis Group, 2021)
This commentary shares the experience of a hospital pharmacy department in providing healthcare services during the COVID-19 outbreak in Malaysia. During this pandemic, the medication delivery system is redesigned to minimize contact among patients and the health care providers. Also, the remote medication monitoring system was implemented to deliver pharmaceutical care for inpatients. Communication technology was used to assist the pharmacist in medication counseling. QR codes to access videos demonstrating the use of devices were made available for patients. Pharmacists were also tasked with the procurement of personal protective equipment and medications needed requiring special approval from the Ministry of Health.